A Case of Pulmonary Vein Thrombosis Associated With Treatment of Omalizumab - Narukonda, Sandhya (J Investig Med High Impact Case Rep, 2017)
Pulmonary vein thrombosis (PVT) is a challenging diagnosis and has been described in association with or as a complication of pulmonary tumors, lung surgeries, atrial myxoma, and after radiofrequency catheter ablation for atrial fibrillation. There are not many reported cases of PVT associated with medication use. We present a case of a 53-year-old male with a history of severe persistent asthma on omalizumab, who presented with shortness of breath and was found to have PVT on computed tomography scan of the chest. The hypercoagulable workup was normal, and the patient did not have a history of malignancy or pulmonary surgeries. Currently, available data suggest an association between omalizumab use and increased risk of arterial thrombotic events. However, on a literature search, we could not find any reported cases of PVT with omalizumab treatment.